Effects of pricing and fleet structure on the airline fleet assignment problem - Kalafatoğlu, Yasemin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The fleet assignment problem constitutes a significant part of airline costs, given that flight operating costs are directly related to it and the fleeting decision affects passenger revenues. The basic fleet assignment problem overlooks itinerary demands and revenue management. In this study, a mixed integer planning model for fleet assignment that incorporates itinerary-level demands, the Itinerary-based Fleet Assignment Model is solved, utilizing real data from a Turkish and a European airline. A multi-factorial experimental design is constructed to examine the interactions of itinerary-based fares, demand and fleet structure based on their effect on the fleet assignment decision. The design defines levels for each factor, representing a percent change in the fare and demand parameters, and different fleet compositions for the fleet structure. The model is solved to optimality for three datasets, for each level of the factors fare, demand and fleet structure. The results are analyzed by a statistical software with respect to different response variables and the effect of each factor to fleet assignment is investigated. Results indicate that fleeting contribution and passenger losses are strongly related to itinerary pricing, demand, and fleet structure.
Keywords: Airlines -- Cost of operation.; Airlines -- Planning -- Mathematical models.